Asuhan Keperawatan pada Ny. W Keluarga Ny. W Dengan Gangguan Sistem Kardiovaskuler : Hipertensi di Desa Kalibuntu RT 04 RW 03 Kecamatan Losari Kabupaten Brebes - Hanifatun Nasriah; Tati Karyawati; Arisnawati Arisnawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The epidemiological transition from infectious diseases to non-communicable diseases is expected to occur massively in 2030, both at the regional, national, and global levels. It is estimated that the number of deaths due to non-communicable diseases and accidents will increase. According to the World Health Organization (WHO), non-communicable diseases include hypertension, diabetes, coronary heart disease and other chronic diseases (Putri et al., 2023). In 2021, in Brebes Regency, there were 666,732 cases of hypertension in the population aged 15 years and over. Around 257,361 hypertension sufferers have visited health services (Fadriana & Wilis, 2023).